“性育”的底线：以张竞生主编的《新文化》月刊为中心 = The bottom-line of “sex education” : focusing on the Journal New Culture, edited by Zhang Jingsheng - 許维贤 Hee, Wai Siam (2012)
本文爬梳和重估張競生主編的《新文化》對「性育」的倡導。這些倡導在推動「知識／權力」對中國男女的「生物性別」、「社會性別」和「性相」的掌控和重新編碼。張競生推崇「優生學」和「美的性交」，以此種「性育」企圖改善中國人身體的先天衰弱和「男不男女不女」的「生物性別」特徵；在衣食住行上鼓吹「美育」，對中國男女「社會性別」各自所缺乏或顛倒的「男性氣概」和「女性氣質」給予「補救」和「矯正」；張競生也通過《性史》徵文和《新文化》來函的收集和分析，辨識中國男女的「性相」，以「按語」嘗試救治其中的「性變態者」。最後，本文也把《新文化》和20年代中國其他雜誌的性別譯述和論述做個比較。發現《新文化》在處理「同性愛」和「性美」的議題上，其作者群幾乎一律「統一」的見解，有時候反而不及《教育雜誌》、《婦女雜誌》和《新女性》對各種不同意見的包容立場。= This article explores and re-evaluates Zhang Jingsheng's ＂Sex Education＂ in his ＂New Culture＂, which advocates controlling and re-coding Chinese men's and women's ＂sex,＂ ＂gender,＂ and ＂sexuality＂ by means of ＂knowledge/power.＂ Zhang Jingsheng accords great value to ＂eugenics＂ and ＂aesthetic sexual intercourse,＂ including the ＂sex education,＂ based upon which he tries to make improvements in Chinese people's innate physical weakness and ＂neither male nor female＂ ＂sex＂ characteristics; and with touted ＂aesthetic education＂ on all of the basic aspects of life, he attempts to remedy and correct the lacked or inverted masculinity and femininity in Chinese men's and women's ＂gender.＂ He also makes his comments on how to save and cure those ＂sex perverts＂ identified in Chinese men's and women's ＂sexualities,＂ the information of which he collected from and analyzed in the articles solicited on the topic of ＂Sexual Histories＂ as well as the letters to ＂New Culture.＂ Finally, this article compares ＂New Culture＂ with those discourses or translated discourses on sexual difference published in other Chinese magazines in the twenties, and concludes that ＂New Culture＂ seems to have a group of writers holding ＂unified＂ opinions on the issues of ＂homosexual love＂ and ＂sexual aesthetics＂ and seems less tolerant of differing opinions than magazines like ＂The Chinese Educational Review, The Ladies' Journal,＂ and ＂New Women.＂